Novel Insights into Trenching of Ni-Containing Low Alloy Steel in Simulated Sour Conditions with Sodium Thiosulfate - Samusawa, Itaru; Shimamura, Junji; Al Helal, Ammar; Sapanathan, Thaneshan (2025)
There is interest in using thiosulfate as a simulant for research on the sour corrosion of carbon steel because of its safety compared to the original sour test using H2S gas. The effect of Ni on trenching behavior using a simulated sour solution containing 10−3 M Na2S2O3 with pH 4.0 was investigated using a four-point bending test in various applied and open-circuit potential conditions. In this study, x-ray diffraction and scanning electron microscopy were used to characterize steel surfaces after testing. The results showed that Ni promotes trenching and is especially favored by anodic constant potential conditions. On the other hand, the amount of H2S generated by the dissociation and reaction of Na2S2O3 with the metal surface during the test was also influenced by Ni content and applied potential. Specifically, the alloying of Ni and the increase in potential promoted H2S formation. Moreover, the H2S concentrations on the steel surface during the tests at pH 4.0 in this study were estimated to correspond to the sour region 0, which is lower than previously reported test at pH 2.7. This indicates that the simulated sour test is more difficult to control H2S concentration than in our earlier sour test with actual H2S gas and found that the amount of H2S generated on each test condition must be taken into consideration carefully when investigating the corrosion behavior in a simulated sour solution containing Na2S2O3. Based on the experimental findings, the trenching mechanism of Ni-containing steel low alloy steel under 10−3 M Na2S2O3 containing acid brines with pH4.0 is proposed.